Astral hydrogels mimic tissue mechanics by aster-aster interpenetration - Qingqiao Xie (Nature Portfolio, 2021)
The development of tissue-like materials which replicate the mechanical properties of tissue is of interest for a range of applications. Here, the authors report on the development of radial asters that form a gel network to stiffen in compression and soften in extension, resembling tissue mechanics.